One new species and one new record of the species of the family Comesomatidae (Nematoda: Chromadorida) from the South China Sea - Huang, Mian; Jia, Susu; Huang, Yong (Zootaxa, 2018)
One new and one known species of the family Comesomatidae were collected from marine sediments in the South China Sea. Cervonema longispicula sp. nov. has stout cephalic setae, elongated and curved spicules with cephalated proximal end, and gubernaculum with hook-like dorsal apophysis that make the new species easily recognizable from the other 18 recorded Cervonema species. Paracomesoma zhangi Huang & Huang, 2018 was redescribed based on more specimens of males and females. These specimens are in accordance with the characteristics of holotype from the East China Sea except having more precloacal supplements (30–39), males slightly smaller (not longer than 1710 µm) and with shorter cephalic setae (not longer than 10 μm).